Assessment of Fumonisin, Deoxynivalenol, and Zearalenone Levels and the Occurrence of Mycotoxigenic Fusarium Species in Cereal Grains from Muscat, Sultanate of Oman - Fatma Khuseib Hamed Al-Rashdi; Abdullah Mohammed Al-Sadi; Mostafa Ibrahim Waly; Shah Hussain; Rethinasamy Velazhahan (Agriculture)
Mycotoxin contamination in agricultural goods is a major global problem due to its negative impact on human and animal health. The principal mycotoxin producers are fungal species from the genera Fusarium, Aspergillus, Alternaria, and Penicillium. The toxigenic fungal species produce the mycotoxins as secondary metabolites when they invade agricultural commodities during crop cultivation in the field (preharvest) or after harvesting or during transport and storage. This study was designed to investigate the levels of Fusarium mycotoxins, viz., fumonisin (FUM), zearalenone (ZEN), and deoxynivalenol (DON) in cereal grain samples collected from Muscat, Sultanate of Oman during 2023-24. A total of 90 cereal grain (wheat, corn, rice, barley) samples from local markets at Muscat, the Plant Quarantine Department, Oman, and Oman Flour Mills Company were analyzed using competitive enzyme immunoassay kits. Furthermore, Fusarium spp. associated with the contaminated grain samples were isolated, and their mycotoxin-producing potential was assessed. The results indicated that FUM, ZEN, and DON levels were below the detection limit (LOD) in 81%, 97%, and 44% of the samples, respectively. Two out of fifteen corn samples and one out of thirty-seven wheat samples tested exceeded the maximum permissible limit for FUM and ZEN, respectively, as set by the European Commission. A total of 19 Fusarium spp. associated with the contaminated grain samples were isolated and identified through molecular techniques. Sixteen isolates of F. verticillioides, one isolate of F. thapsinum, and two new Fusarium species were identified based on nuclear ribosomal DNA internal transcribed spacer and elongation factor 1-alpha sequences. Two isolates of F. verticillioides (FQD-1 and FQD-20) produced FUM levels exceeding 2000 µg kg−1. The maximum ZEN concentration was observed in F. verticillioides FQD-20 (9.2 µg kg−1), followed by F. verticillioides FQD-2 (2.8 µg kg−1) and Fusarium sp. FOFMC-26 (2.5 µg kg−1). All tested Fusarium strains produced DON, with levels ranging from 25.6 to 213 µg kg−1, with F. thapsinum FQD-4 producing the highest level (213 µg kg−1). To our knowledge, this is the first report on the occurrence of Fusarium mycotoxins and mycotoxigenic Fusarium spp. in food commodities in Oman.